Peningkatan Keterampilan Pengelolaan Website Bagi Warga Pengelola Desa Wisata Cisaat - Bahtiar, Ihwan Rahman; Failasuf, Chakam; Jubaidah, Siti (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2024)
Cisaat Tourism Village is one of the villages in Subang Regency that has received website facilities both as a public service media and tourism promotion. However, due to limited human resources, the website management of Cisaat Tourism Village is not optimal. This community service activity aims to provide Cisaat Tourism Village managers with training on website management skills. This community service activity was conducted offline for two days using the Participatory Technology Development and Participatory Rural Appraisal (PRA) approaches. Technically, this service activity is divided into three stages: preparation, implementation, and evaluation. Based on the evaluation results obtained, the service activities succeeded in increasing the knowledge and skills of the participants in managing the village website. In addition, the new skills acquired by the participants also inspired them to utilize the website as a medium for service and promotion of tourism in Cisaat Tourism Village.